The Linkage Between Speculative Attack and Target Zone Models of Exchange Rates. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
In this paper we generalize the target zone exchange rate as model formalized by Krugman (1988b). The main contributions of these pages consist of linking the recent developments in the theory of target zones to the mirror image theory of speculative attacks on asset price fixing regimes and in using aspects of that linkage to give an intuitive interpretation to the 'smooth pasting' condition often invoked as a terminal condition. We aim to unify these two literatures by showing that the solution concepts in both are identical.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet